Change in upper airway dimensions after orthodontic surgical treatment: Case report (Research, Society and Development, 2024)
Sleep Apnea Hypopnea Syndrome has continuous positive air pressure devices as the gold standard treatment. However, other treatment options can be performed, such as maxillomandibular orthognathic surgery. Knowing that facial pattern II is an aggravating factor for apnea, we present a clinical case of a 52-year-old female patient who sought orthodontic treatment. There were complaints of pain in the TMJ region, difficulty in chewing, daytime fatigue and sleep apnea. In the intraoral aspect, the patient was bilaterally class II, with deep overbite, left unilateral crossbite (with implants already present), old prostheses, multiple tooth loss and mesially inclined lower molars. The objective of the treatment was to advance the mandible, correct the crossbite and leave spaces for the new implant prostheses. After treatment, the patient showed symptomatic improvement of apnea. We can make a comparison with cephalometrics using the analysis of the airway before and after the treatment. It was also possible to compare in volume and air the size of the airway before and after surgery using computed tomography and the dolphin program. Before the surgery, the patient had a volume of 20152 mm3 and an area of 701 mm2, after the surgery she had a volume of 23145 mm3 and 782 mm2. More studies showing the long term and a greater number of patients are needed to document the results and have a better predictability of the indication of this type of surgical approach for the treatment of the syndrome.